PENGEMBANGAN MEDIA PINBALL MATEMATIKA TERHADAP PENINGKATAN NUMERASI PENJUMLAHAN BILANGAN CACAH MURID SEKOLAH DASAR - Noval Saputra, Rizky; Indarini, Endang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of primary school students' numeracy skills in whole number addition, combined with the lack of relevant interactive learning media, underlies the necessity of this Research and Development (R&D) study. This study aims to develop "Math Pinball" media and evaluate its validity, effectiveness, and practicality in optimizing students' numeracy skills. Adopting Sugiyono's R&D framework integrated with the ADDIE model, the development process comprised seven distinct stages. The product was tested on second-grade students at SDN Ujung-Ujung 03. Data were collected using expert validation sheets, achievement tests (pretest and posttest), and response questionnaires, which were subsequently analyzed using quantitative descriptive statistics and a Paired Sample T-Test. The results demonstrated high validity, with material and media experts awarding scores of 93.18% and 95.8%, respectively, categorizing the product as "very high." In terms of effectiveness, a substantial improvement in numeracy skills was observed from pretest to posttest across three key indicators: identifying information (65% to 91%), determining solution strategies (64% to 92%), and calculating results (66% to 89%). The Paired Sample T-Test yielded a significance value of Sig. (2-tailed) = 0.001 (p < 0.05), confirming a statistically significant positive impact on learning outcomes. Furthermore, the media achieved a high level of practicality, receiving a 97% approval rating from the teacher and 91% from students, categorizing it as "very practical." Consequently, the Mathematic Pinball media is proven to be valid, effective, and practical for reinforcing whole number addition numeracy in primary education.